2021
DOI: 10.3390/ijerph181910370
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Oxygen Production-Related Greenhouse Gas Emissions by Improved Compression Heat Management in a Cryogenic Air Separation Unit

Abstract: Oxygen production in cryogenic air separation units is related to a significant carbon footprint and its supply in the medicinal sphere became critical during the recent COVID-19 crisis. An improved unit design was proposed, utilizing a part of waste heat produced during air pre-cooling and intercooling via absorption coolers, to reduce power consumption. Variable ambient air humidity impact on compressed air dryers’ regeneration was also considered. A steady-state process simulation of a model 500 t h−1 inlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 77 publications
(109 reference statements)
0
4
0
Order By: Relevance
“…Emission factors from electricity production are known to vary significantly depending on the energy mix and other conditions considered in their evaluation [83,84]. As discussed in our recent study [85], the emission factor of CO 2 can vary between close to zero values for an almost exclusively renewable energy-based mix up to 700 to 900 kg/MWh for coaland oil-fired power plants. Adopting a value of 700 kg/MWh [86] instead of that from Table 5 (136 kg/MWh) substantially changes the resulting global CO 2 balance of increased steam import into SC: global increase in CO 2 emissions of 5600 t/year changes to the reduction of approximately 900 t/year.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Emission factors from electricity production are known to vary significantly depending on the energy mix and other conditions considered in their evaluation [83,84]. As discussed in our recent study [85], the emission factor of CO 2 can vary between close to zero values for an almost exclusively renewable energy-based mix up to 700 to 900 kg/MWh for coaland oil-fired power plants. Adopting a value of 700 kg/MWh [86] instead of that from Table 5 (136 kg/MWh) substantially changes the resulting global CO 2 balance of increased steam import into SC: global increase in CO 2 emissions of 5600 t/year changes to the reduction of approximately 900 t/year.…”
Section: Discussionmentioning
confidence: 84%
“…Li et al (2019) [95] studied the environmental performance of a high-temperature heat pump-assisted gas separation plant located in China within a more complex frame of energy, exergy, economic and environmental optimization of the given plant, yielding achievable savings in CO 2 , NO x , and SO 2 emissions. Finally, the authors themselves applied the balances of CO 2 , NO x, and SO x emissions based on fuel composition and field emissions data in their earlier studies on refinery processes [38] or oxygen production plant [85] optimization. It can be concluded that, while all mentioned approaches are viable, using available field data ensures the validity of the environmental assessment results both generally and in a particular on-site application.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of an energy-efficient material for the swing absorption of O 2 remains highly sought for a wide range of applications from O 2 supplies to COPD patients, to aircraft and submarine emergency O 2 supplies, and for separation from H 2 in water electrolysis to name just a few. The typical energy consumption in units for the cryogenic separation of O 2 from air exceeds 200 kWh of electricity per ton of produced oxygen and is thus associated with significant environmental impact. , Despite the eight intervening decades since Calvin and co-worker’s impressive studies using 42 variations on the Co­(salen) scaffold, and which were deemed highly important for the U.S. National Defense, no advance has been made. At that time, however, no SAR insight through crystallographic characterization was possible.…”
Section: Discussionmentioning
confidence: 99%
“…As to obtain yet more data for model verification, a model for condensing power production only was set-up and presented elsewhere [110]. Specific steam production for condensing power production of over 4.5 t MWh -1 and net electric efficiency of 30.6% are within the range of performance parameters of subcritical sub-100 MW scale thermal power plants listed in reference literature [68,80].…”
Section: Basic Chp Model Verificationmentioning
confidence: 99%